ANALISIS FAKTOR MOTIVASI YANG MEMPENGARUHI PRESTASI BELAJAR SISWA PADA BIDANG STUDI MATEMATIKA DI SEKOLAH MENENGAH PERTAMA NEGERI 1 NAMLEA - Zakaria, Yusran; Umanailo, M. Chairul Basrun; Lisaholit, Syafa; Chamidah, Dina (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of motivation on mathematics learning achievement of students at Namlea 1 Middle School. This research is a form of research "Ex Post Facto" which is a research model that aims to examine the events that have occurred. The subjects in this study were all students of class VIIa of Middle School 1 Namlea, totaling 30 people. Data collection techniques using observation techniques, questionnaires and study documentation. Quantitative data analysis was carried out using statistical tests through three stages, namely the stage of data description, the prerequisite test phase of analysis and the stage of testing the hypothesis. Based on the results of the study note that the level of motivation and learning achievement of eighth grade students at Namlea Middle School 1 is categorized high. Associatively, the motivating factor has a positive and significant effect on mathematics learning achievement in class VIIa State Middle High School 1 Namlea.